Poly-LacNAc as an Age-Specific Ligand for Rotavirus P[11] in Neonates and Infants - Liu, Yang (Public Library of Science, 2013)
Rotavirus (RV) P[11] is an unique genotype that infects neonates. The mechanism of such age-specific host restriction remains unknown. In this study, we explored host mucosal glycans as a potential age-specific factor for attachment of P[11] RVs. Using in vitro binding assays, we demonstrated that VP8* of a P[11] RV (N155) could bind saliva of infants (60.3%, N = 151) but not of adults (0%, N = 48), with a significantly negative correlation between binding of VP8* and ages of infants (P<0.01). Recognition to the infant saliva did not correlate with the ABO, secretor and Lewis histo-blood group antigens (HBGAs) but with the binding of the lectin Lycopersicon esculentum (LEA) that is known to recognize the oligomers of N-acetyllactosamine (LacNAc), a precursor of human HBGAs. Direct evidence of LacNAc involvement in P[11] binding was obtained from specific binding of VP8* with homopolymers of LacNAc in variable lengths through a glycan array analysis of 611 glycans. These results were confirmed by strong binding of VP8* to the Lec2 cell line that expresses LacNAc oligomers but not to the Lec8 cell line lacking the LacNAc. In addition, N155 VP8* and authentic P[11] RVs (human 116E and bovine B223) hemagglutinated human red blood cells that are known to express poly-LacNAc. The potential role of poly-LacNAc in host attachment and infection of RVs has been obtained by abrogation of 116E replication by the PAA-conjugated poly-LacNAc, human milk, and LEA positive infant saliva. Overall, our results suggested that the poly-LacNAc could serve as an age-specific receptor for P[11] RVs and well explained the epidemiology that P[11] RVs mainly infect neonates and young children.